An Analysis of the Rotation and Mutation Mechanism of State Civil Apparatus Positions - Arti Putri Apandi; Andi Mulyadi; Dian Purwanti (LifeSciFi, 2026)
The implementation of State Civil Apparatus (Aparatur Sipil Negara/ASN) rotation and mutation policies supports bureaucratic professionalism, organizational effectiveness, and merit-based management, but faces challenges in transparency, communication, political influence, and human resource capacity. The objective of this study is to analyze ASN rotation and mutation mechanisms in Sukabumi City, focusing on transparency, decision-making, and compliance with merit-based principles and regulations. This study applied a qualitative descriptive method using interviews and documentation analysis, with data analyzed through reduction, presentation, and conclusion drawing. The findings show that the implementation of rotation and mutation policies has been strengthened by clear regulations, technology-based talent management systems such as I-MUT and SIMATA ASN BKN, nine-box talent mapping, and competency-based assessment mechanisms. These systems improve transparency, objectivity, and efficiency in personnel placement. However, several challenges remain, including limited ASN regeneration due to retirement and recruitment imbalance, communication barriers, limited information disclosure to employees, lengthy bureaucratic procedures, and the potential influence of political considerations in final decisions. The study concludes that effective implementation requires not only regulations and digital systems but also strong communication, leadership commitment, and consistent merit principles. This research contributes insights into merit-based personnel management and supports more transparent, accountable, and professional bureaucracy.